Legal Review of the Transfer of Fiduciary Guarantee Objects and the Legal Responsibilities of Creditors-Debtors - S. Said; Indra Yuliawan; Arista Candra Irawati (Golden Ratio of Data in Summary, 2026)
Fiduciary security plays a central role in modern security transactions by allowing creditors to obtain enforceable ownership rights over movable assets, while debtors retain physical possession of the collateral. The effectiveness of fiduciary security depends not only on the creation of enforceable ownership rights in the event of default but also on the clear allocation of legal liability between the debtor and creditor when the pledged assets are transferred to another party. The transfer of fiduciary security objects gives rise to complex legal issues regarding the continuity of ownership rights. This article discusses: (1) how fiduciary security generates enforceable ownership rights in security transactions; and (2) how the responsibilities of the debtor and creditor toward the fiduciary security object shift when it is transferred to another party. This study employs a doctrinal legal research method, combining a statutory approach to analyze the normative framework of fiduciary security with a conceptual approach to examine ownership rights and debtor-creditor liability, as well as the judicial interpretation of Law Number 42 of 1999 concerning Fiduciary Security, specifically Constitutional Court Decision No. 18/PUU-XVII/2019 and Constitutional Court Decision No. 2/PUU-XIX/2021.